If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + 4 = x Reorder the terms: 4 + -7x = x Solving 4 + -7x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 4 + -7x + -1x = x + -1x Combine like terms: -7x + -1x = -8x 4 + -8x = x + -1x Combine like terms: x + -1x = 0 4 + -8x = 0 Add '-4' to each side of the equation. 4 + -4 + -8x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -8x = 0 + -4 -8x = 0 + -4 Combine like terms: 0 + -4 = -4 -8x = -4 Divide each side by '-8'. x = 0.5 Simplifying x = 0.5
| 0=2x-17 | | 5-9+=6+2-3 | | -7(x+3)-10=31+1 | | -3z-8=10 | | 10x-5x-3=-2 | | 9-8=8 | | 4x^4-12x^3+3=0 | | 5(4x-3)+x=7(3x+2) | | -2y-13=6y+19 | | -8(x-2)+2=58 | | 9y+12y=63 | | 7x=96-x | | -2(11-4c)=11(c-8) | | 9y+7.7=-4.5 | | 8(-2)=16 | | 5y+7=62 | | 4(x+12)-5=79 | | (x-1)(3x-5)(4x-8)=0 | | X-5=9x-9 | | 1/2=78 | | 7.87=26.25+.5a(2.5) | | 124-5x=40x+19 | | 3x^2-6=6y | | 7.87=26.25+.5(2.5) | | -5(x+7)-42=2-49 | | -5-4=21 | | x-7.7=-4.5 | | 2x^3+5x^2+6x-27=0 | | s-22=-33 | | 3(2x-3)=1-7x | | x^4-0x^3-73x^2-72x=0 | | -6x+4=-8x |